Expansion of the Liver Donor Supply Through Greater Use of Split‐Liver Transplantation: Identifying Optimal Recipients. Issue 1 (4th January 2019) - Mogul, Douglas B.; Luo, Xun; Garonzik‐Wang, Jacqueline; Bowring, Mary G.; Massie, Allan B.; Schwarz, Kathleen B.; Cameron, Andrew M.; Bridges, John F. P.; Segev, Dorry L.
Abstract : The increased use of split‐liver transplantation (SLT) represents a strategy to increase the supply of organs. Although outcomes after SLT and whole liver transplantation (WLT) are similar on average among pediatric recipients, we hypothesized that the relationship between graft type and outcomes may vary depending on patient, donor, and surgical characteristics. We evaluated graft survival among pediatric (<18 years) deceased donor, liver‐only transplant recipients from March 2002 until December 2015 using data from the Scientific Registry of Transplant Recipients. Graft survival was assessed in a Cox proportional hazards model, with and without effect modification between graft type and donor, recipient, and surgical characteristics, to identify conditions where the risk of graft loss for SLT and WLT were similar. In a traditional multivariable model, characteristics associated with graft loss included donor age >50 years, recipient weight <10 kg, acute hepatic necrosis, autoimmune diseases, tumor, public insurance, and cold ischemia time (CIT) >8 hours. In an analysis that explored whether these characteristics modified the relationship between graft type and graft loss, many characteristics associated with loss actually had similar outcomes regardless of graft type, including weight <10 kg, acute hepatic necrosis, autoimmune diseases, and tumor. In contrast, several subgroups had worse outcomes when SLT was used, including recipient weight 10‐35 kg, non–biliary atresia cholestasis, and metabolic disease. Allocation score, share type, or CIT did not modify risk of graft type and graft failure. Although one might anticipate that individuals with higher rates of graft loss would be worse candidates for SLT, data suggest that these patients actually have similar rates of graft loss. These findings can guide surgical decision making and may support policy changes that promote the increased use of SLT for specific pediatric recipients.